Escola cidadã e colegiados escolares: desafios e possibilidades - Dias, Monica Roberta Devai (2016)
The object of the investigation was to the performance of the school collegiate as one of the democratic management strategies committed to the promotion of the quality of education. The strategies carried out by the management team were evaluated in order to promote ways for the school to consolidate itself in a fully democratic space, even if it presented movements of advances and retreats in its trajectory. For this research the following problems were raised: Was the school collegiate as an organ of support able to articulate the community as a whole? This articulation implied in the quality of teaching of the students? Has the manager's profile contributed to the success of school colleges? The universe assigned to carry out this research was a Municipal School of Early Childhood Education and Primary Education that serves children from three to ten years in the city of Santo André, Grande ABC, metropolitan region of São Paulo. The members of this research were the segments: management team, employees, teachers, parents and children's council, who were elected to participate in school colleges. The qualitative methodology was based on the collection of data, obtained in semi-structured interviews and in dialogical actions as circles of culture supported by a critical theoretical reference. Government documents and determinations will be analyzed in the scope of the school management and of public policies that support them and foster the implantation of the collegiate ones such as: Federal Constitution of 1988; The Law of Guidelines and Basis of National Education of 1997 (LDBEN); National Education Plan 2014/2024 (PNE); National Program to Strengthen School Boards and municipal laws to promote collegiate education. The analysis was processed from records collected at collegiate meetings, recorded audios and photos at times of actions execution. The references were based on the contributions of Gramsci (1979) and Nosella (2010) to clarify the categories of ideology and alienation, hegemony and counter-hegemony in their articulation with Paulo Freire (1997, 2005a, 2005b, 2014), particularly in the Conceptual use of world reading, dialogic action and awareness. Secondary references have come from authors who study the themes of democratic management, Romão (1992, 2006, 2010), to support the categories of citizenship school, Gadotti (2010, 2014), Licínio (2002), Antunes (2002a) and Padilha ).